Impact of the KidneyWise toolkit on chronic kidney disease referral practices in Ontario primary care: a prospective evaluation - Brimble, Kenneth Scott (BMJ Open, 2020)
OBJECTIVES: Chronic kidney disease (CKD) is common; therefore, coordination of care between primary care and nephrology is important. Ontario Renal Network’s KidneyWise toolkit was developed to provide guidance on the detection and management of people with CKD in primary care (www.kidneywise.ca). The aim of this study was to evaluate the impact of the April 2015 KidneyWise toolkit release on the characteristics of primary care referrals to nephrology. DESIGN AND SETTING: The study was a prospective pre-post design conducted at two nephrology sites (community site: Trillium Health Partners in Mississauga, Ontario, Canada, and academic site: St Joseph’s Healthcare in Hamilton, Ontario, Canada). Referrals were compared during the 3-month time period immediately prior to, and during a 3-month period 1 year after, the toolkit release. PRIMARY AND SECONDARY OUTCOME MEASURES: The primary outcome was the change in proportion of referrals for CKD that met the KidneyWise criteria. Additional secondary referral and quality of care outcomes were also evaluated. Multivariable logistic regression was used to evaluate preselected variables for their independent association with referrals that met the KidneyWise criteria. RESULTS: The proportion of referrals for CKD among people who met the KidneyWise referral criteria did not significantly change from pre-KidneyWise to post-KidneyWise implementation (44.7% vs 45.8%, respectively, adjusted OR 1.16, 95% CI 0.85 to 1.59, p=0.36). The proportion of referrals for CKD that provided a urine albumin-creatinine ratio significantly increased post-KidneyWise (25.8% vs 43.8%, adjusted OR 1.45, 95% CI 1.06 to 1.97, p=0.02). The significant independent predictors of meeting the KidneyWise referral criteria were academic site, increased age and use of the KidneyWise referral form. CONCLUSIONS: We did not observe any change in the proportion of appropriate referrals for CKD at two large nephrology centres 1 year after implementation of the KidneyWise toolkit.